State and perspectives of using of land for transport in Ukraine - Stetsyuk, M.; Ishchenko, N. (Land Management, Cadastre and Land Monitoring, 2018)
Globalization and Eurointegration in the conditions of institutional transformations in Ukraine show a significant role for the transport sector in the development of such processes. Transport and  warehousing  are providing different production and non-production needs of institutional units and the population of the country in all types of transportation. Also these branches of economy amount to 6.6% of GDP in the national economy of Ukraine in 2015. The active reforms of recent years relate in particular the implementation of the Ukraine-2020 Sustainable Development Strategy, the implementation of the Association Agreement between Ukraine and the EU, which envisages an in-depth and comprehensive free trade zone, indicates the external and internal priority of Ukraine in the development of  transport .The task of  the  research  is  the  systematization  the land transport concept, also analyze trends in land use for such purposes in terms of land owners and land users, as well as outline the prospects for land use of the transport sector in Ukraine.The legislation of Ukraine that considers land transport, is able to set restrictions on their use, special land use regime or protection zones. In particular, restrictions are available on approaches to ports (channels), bridge, cable and air transitions, water intakes and other objects on the land of sea transport; special regime of land use - at aerodrome territory of land of aviation transport; security zones - along the ground, above ground and underground pipelines.The role of land used for transport is one of the main components of the territorial division of labor and a means of ensuring territorial interconnections, as well as a link between production and consumption. It should be noted that transport infrastructure influences economic relations between regions and countries as a whole.The tendency of development of the transport sector of Ukraine in accordance with the provisions declared in the legislation and international agreements obviously requires significant changes in land use. However, draft laws and international agreements show a significant potential and prospects for the development of all transport sectors in Ukraine. There have been trends in the growth of the land used for transport since 2000, as well as the reduction of land under railways and airports and the increase of land under roads in 2015. These trends indicate active changes in the sector that require further research. in the context of certain sectors of transport. Prospects for further research are also the justification of organizational and legal prerequisites and financial and economic incentives for investment and the development of public-private partnerships in order to improve the quality of maintenance, repair and modernization of transport infrastructure.Keywords: land categories, land use, strategy, land accounting, restructuring and updating the transport sector of Ukraine.